Arabidopsis casein kinase 2 α4 subunit regulates various developmental pathways in a functionally overlapping manner - Mulekar, Jidnyasa Jayant (Plant science : an international journal of experimental plant biology, 2015)
Copyright © 2015 Elsevier Ireland Ltd. All rights reserved.